2010
DOI: 10.1007/s00442-010-1750-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity in the relative impacts of foliar quality and predation pressure on red oak, Quercus rubra, arthropod communities

Abstract: Predation pressure and resource availability often interact in structuring herbivore communities, with their relative influence varying in space and time. The operation of multiple ecological pressures and guild-specific herbivore responses may combine to override simple predictions of how the roles of plant quality and predation pressure vary in space. For 2 years at the Coweeta LTER in the Southern Appalachian Mountains, we conducted a bird exclosure experiment on red oak (Quercus rubra) saplings to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Parasitism and predation on herbivorous insects and the density of predatory groups frequently decrease with elevation (Bowden & Buddle, 2010; Hodkinson, 2005; Pepi et al, 2017). However, other studies did not find any elevational trends in bird predation on arthropods (Schwenk et al, 2010; Zehnder et al, 2010). In particular, a bird exclusion experiment previously conducted in three of our six gradients showed similar effects of bird predation on insect herbivory in alpine tundra and in lowland forests (Zverev et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…Parasitism and predation on herbivorous insects and the density of predatory groups frequently decrease with elevation (Bowden & Buddle, 2010; Hodkinson, 2005; Pepi et al, 2017). However, other studies did not find any elevational trends in bird predation on arthropods (Schwenk et al, 2010; Zehnder et al, 2010). In particular, a bird exclusion experiment previously conducted in three of our six gradients showed similar effects of bird predation on insect herbivory in alpine tundra and in lowland forests (Zverev et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…1A). However, several other studies assessing changes in both enemy abundance and pressure have found no elevational patterns (McMillin andWagner 1998, Roininen et al 2006), and other authors that have reported expected decreases in parasitoid diversity or predator abundance with elevation have not found concomitant elevational gradients in parasitism or predation (Straw et al 2009, Tantowijoyo and Hoffmann 2010, Zehnder et al 2010. In these latter studies, elevational gradients in insect herbivore abundance and plant damage were presumably influenced by abiotic factors that directly (or indirectly via effects on host plants) influence herbivores rather than via indirect defence.…”
Section: Tritrophic Interactions Influence Plant-insect Herbivore Elementioning
confidence: 99%
“…However, the strength or even the direction of elevational changes in these interactions can differ between trophic levels because this type of variation was previously detected in latitudinal gradients: herbivory and carnivory decreased from low to high latitudes, whereas parasitism increased (Zvereva & Kozlov, 2021). For elevational gradients, any particular predictions about variations among trophic levels are hampered by a lack of reviews of elevational changes in carnivory and by inconsistent results of a few primary studies that measured carnivory and herbivory within the same elevational gradients (Bito et al, 2011; Oksanen et al, 1981; Zehnder et al, 2010). Therefore, we could only anticipate that (2) the strength of elevational changes differs between herbivory, carnivory and parasitism.…”
Section: Introductionmentioning
confidence: 99%